Comparative efficacy of sodium benzoate and potassium sorbate as preservative in candied kamias - Parce, Carmina J.
The preservative effect of sodium benzoate and potassium sorbate in candied kamias was determined by evaluating their antimicrobial activity against microorganisms isolated from the candied product itself. These microorganisms, consisting of 3 species of bacteria, one type of yeast and a mold, were introduced to samples which have been previously dipped in 2%, 3%, and 4% solutions of the preservative. Microbial examinations were conducted before and after six weeks storage. Benzoate was found more effective than sorbate in controlling yeasts and molds but sorbate exhibited greater activity against bacteria. Benzoate was effective even at 2% dipping solution whereas sorbate was equally effective at higher concentrations. The samples absorbed 662 ppm sorbate from 2% dipping while 2% benzoate solution deposited 576 ppm benzoate. Sensory evaluation showed that both benzoate ad sorbate were not detectable at the 2% level but sorbate treated samples were more acceptable. 2% potassium sorbate dipping was considered adequate enough in controlling microbial growth without impairing the flavor of candied kamias.